2021
DOI: 10.21037/tau-21-445
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related long non-coding RNAs can serve as prognostic biomarkers for clear cell renal cell carcinoma

Abstract: Background:The immune microenvironment is a critical regulator of clear cell renal cell carcinoma (ccRCC) progression. However, the underlying mechanisms the regulatory role of immune-related long non-coding RNAs (irlncRNAs) in the ccRCC tumor microenvironment (TME) are still obscure. Herein, we investigated prognostics role of irlncRNAs for ccRCC. Methods:The raw data of patients with ccRCC were downloaded from The Cancer Genome Atlas (TCGA) database, and immune-related genes were obtained from the ImmPort da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…So immune checkpoint inhibitors which block PD1/PDL1 or CTLA4 have been proven effective and considered as standard treatment [ 11 , 36 ]. In our study, we have found that the risk score is positively related to Tregs, which is consistent with previous studies [ 37 ]. And we also found that CTLA4 expression, CD247 expression, LAG3 expression, PDCD1 expression, and TIGIT expression were positively related to the risk score, which means that this model has a potential predictive significance for the efficacy of immune checkpoint inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…So immune checkpoint inhibitors which block PD1/PDL1 or CTLA4 have been proven effective and considered as standard treatment [ 11 , 36 ]. In our study, we have found that the risk score is positively related to Tregs, which is consistent with previous studies [ 37 ]. And we also found that CTLA4 expression, CD247 expression, LAG3 expression, PDCD1 expression, and TIGIT expression were positively related to the risk score, which means that this model has a potential predictive significance for the efficacy of immune checkpoint inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…In DEG cluster analysis, we found that the high abundance of macrophages M0 in class B shortened the overall survival of ccRCC patients, and the opposite was true in class A. Previous studies have demonstrated that immunosuppressive cells, such as M0 macrophages, are higher in high-risk ccRCC patients, while the proportion of active immune cells, including naive B cells, resting CD4 memory T cells, resting natural killer (NK) cells were lower, indicating the presence of an immunosuppressive microenvironment [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 82%
“…[40] The ceRNA hypothesis suggests that lncRNAs can influence the production of messenger RNAs (mRNAs) relevant to fatty acid (FA) metabolism by acting as sponges for microRNAs (miRNAs) in ccRCC. While several studies have established ceRNA networks in ccRCC, [29][30][31][32] the specific regulatory role of FA metabolism-related ceRNA is still not well understood. This study conducted a detailed analysis of the genomic information from 539 ccRCC samples to evaluate the pattern of FA metabolism and develop a predictive risk score model for FA.…”
Section: Introdutionmentioning
confidence: 99%
“…[27,28] Several researchers have investigated the expression profiling of lncRNA in ccRCC and have discovered that they can function as biomarkers for the diagnosis and prognosis of ccRCC. [29][30][31][32] Recent investigations have shown that lncRNAs play a role in controlling the expression of important genes, as well as networks of genes involved in processes related to cholesterol and FA production, reverse cholesterol transport, and lipid storage. [33][34][35] LncRNAs also seem to selectively affect many transcription factors that have crucial functions in controlling lipid metabolism, including liver X receptors, [36] sterol regulatory element binding proteins, [37,38] and peroxisome proliferator-activated receptor α (PPARα).…”
Section: Introdutionmentioning
confidence: 99%